ASSOCIATION PARANAENSE VETERANS BASKETBALL: HISTORY, EMOTIONS AND SOCIAL MEANING (Fiep Bulletin - online, 2015)
We can say, that to understand society better, is necessary to comprehend it`s social phenomenons, like the manifestations of music groups, arts, dance, folklore, and in our case, sports. To do that, we`ll try to understand the social phenomenon, that is sport, inside one of it´s representation, in this case, the group of Paraná´s Veterans Basketball players. Basketball is a collective sport, very dinamic and exciting, considering the variety of plays and moves, baskets, spectaculars passes and dunks. According to the press, basketball has a great importance in the national view, losing in popularity, only to soccer and voleyball. We can say, that Basketball  went over many barriers to be popularized/institutionalized, and today many groups look for places to play, including former basketball athletes, with 35 years old or more, being that the main characteristic of the veteran basketball player. The practice of veteran basketball, is characterized by it´s constantly search for emotions, pleasure and social meaning. The search for this emotions make the will of practicing basketball alive. We can say, that besides this emotions, there is the fact that the veteran player wants to be a part of a group, and, according to our research, half  of the group practices basketball to participate in competitions and tournaments, and the rest of the group just to be a part of a group, to maintain their relationships. To understand better this relations, we interviewed veteran players from Curitiba and Ponta Grossa, and map this structure and the events promoted by the Associação Paranaense de Veteranos de Basquetebol, institution that promotes all the tournaments and championships, with the objective of socialize and motivate veterans.
Keywords: Veteran Basketball; emotions and social meaning.